Expression of long non-coding RNA DLX6-AS1 in lung adenocarcinoma - Li, Juan (Cancer Cell Int, 2015)
BACKGROUND: Lung adenocarcinoma (LAC), the primary histological type of non-small cell lung cancer (NSCLC), has displayed an increasing incidence and mortality worldwide. However, therapeutic approaches were limited. Dysregulation of some lncRNAs has been shown in various types of cancers including LAC. The aim of the present study was to vertify lncRNA DLX6-AS1 expression in LAC. METHODS: Microarray assay revealed expression profile of lncRNAs in LAC. qRT-PCR ( quantitative reverse transcription PCR) was performed to identify lncRNA DLX6-AS1 expression level in 72 paired LAC and adjacent normal lung tissues. qRT-PCR and Western blotting were used to verify that down-regulation lncRNA DLX6-AS1 decreased DLX6 (distal-less homeobox 6) mRNA and protein expression. RESULTS: Microarray analysis identified up-regulation of 272 lncRNAs and down-regulation of 635 lncRNAs in LAC tissues. The expression level of lncRNA DLX6-AS1 in LAC tissues was significantly higher compared to paired adjacent normal lung tissues (P< 0.05). In addition, its expression level was closed correlated with both histological differentiation (P = 0.004) and TNM stage (P = 0.033). qRT-PCR and Western blotting analysis showed that DLX6 mRNA and protein levels were lower in si-LncRNA group than in the NC (negative control) and Blank groups. CONCLUSIONS: Microarray analysis identified that lncRNA DLX6-AS1 was up-regulated in LAC tissues. High DLX6-AS1 expression levels were significantly associated with both histological differentiation and TNM stage. Down-regulation of lncRNA DLX6-AS1 expression decreased the DLX6 mRNA and protein levels.